Workplace Wellbeing and Job Satisfaction Analysis among Healthcare Workers at a Resource Limited Community Health Clinic in Uganda - Asad Siddiqui; Harish Karthikeyan; Riya Mehta; Fahad Jamal; Rishi Sharma (South Asian Research Journal of Nursing and Healthcare, 2026)
Burnout and job dissatisfaction significantly challenge healthcare systems in low-resource settings, impacting both provider well-being and patient safety. While global burnout rates vary, sub-Saharan Africa often faces intensified pressures due to severe workforce shortages and resource deficits. This study investigated factors influencing workplace satisfaction, stress, and overall well-being among personnel at a community clinic in Kampala, Uganda. It specifically examined the impact of perceived value, occupational roles, workload, and demographics on staff morale. A cross-sectional, descriptive survey was conducted among 31 staff members (75% female; mean age 31.8 years). Data on workplace relationships, stress, and satisfaction were collected through anonymous, structured questionnaires and analyzed using descriptive statistics, Pearson correlation, and ANOVA. Staff reported high overall job satisfaction (mean 3.9/5.0) and a strong sense of community (4.3/5.0). Feeling valued was significantly correlated with higher satisfaction (p=0.042). Clinical roles, particularly the solitary dentist, reported higher stress and lower satisfaction than administrative or support roles. Stress increased steadily as the workweek approached six days, while frequent social interaction with colleagues was strongly associated with lower stress levels (r=-0.53, p